Mental health problems of undocumented migrants (UMs) in the Netherlands: a qualitative exploration of help-seeking behaviour and experiences with primary care - Teunissen, Erik (BMJ Open, 2014)
OBJECTIVE: To explore health-seeking behaviour and experiences of undocumented migrants (UMs) in general practice in relation to mental health problems. DESIGN: Qualitative study using semistructured interviews and thematic analysis. PARTICIPANTS: 15 UMs in the Netherlands, varying in age, gender, country of origin and education; inclusion until theoretical saturation was reached. SETTING: 4 cities in the Netherlands. RESULTS: UMs consider mental health problems to be directly related to their precarious living conditions. For support, they refer to friends and religion first, the general practitioner (GP) is their last resort. Barriers for seeking help include taboo on mental health problems, lack of knowledge of and trust in GPs competencies regarding mental health and general barriers in accessing healthcare as an UM (lack of knowledge of the right to access healthcare, fear of prosecution, financial constraints and practical difficulties). Once access has been gained, satisfaction with care is high. This is primarily due to the attitude of the GPs and the effectiveness of the treatment. Reasons for dissatisfaction with GP care are an experienced lack of time, lack of personal attention and absence of physical examination. Expectations of the GP vary, medication for mental health problems is not necessarily seen as a good practice. CONCLUSIONS: UMs often see their precarious living conditions as an important determinant of their mental health; they do not easily seek help for mental health problems and various barriers hamper access to healthcare for them. Rather than for medication, UMs are looking for encouragement and support from their GP. We recommend that barriers experienced in seeking professional care are tackled at an institutional level as well as at the level of GP.